2023
DOI: 10.1039/d3ta03420h
|View full text |Cite
|
Sign up to set email alerts
|

Covalent conjugation of a ‘hydroxide-philic’ functional group achieving ‘hydroxide-phobic’ TEMPO with superior stability in all-organic aqueous redox flow batteries

Abstract: We show that a covalent conjugation of a ‘hydroxide-philic’ functional group to TEMPO moiety is the key to effectively mitigating chemical degradation during charging and discharging, which hinders OH–-access to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Previous work has indicated that Cl − interferes with OH/O adsorption and causes the formation of Pt-chloro complexes (e.g., [PtCl 4 ] 2− and [PtCl 6 ] 2− ) to become competitive with PtO generation. 38 Second, we found in our earlier work 17 that the electrogenerated [MIMAcO-T + − OH − ] adduct repels OH − , which may cause ΔpH local to deviate from the theoretically expected results. These two factors may contribute to the difference between the experimental and simulated results, which are reflected in the relatively large error bars in Figure 5f.…”
Section: Determination Of Ph Local Affected By Oxidation Of Mimaco-t ...mentioning
confidence: 79%
See 4 more Smart Citations
“…Previous work has indicated that Cl − interferes with OH/O adsorption and causes the formation of Pt-chloro complexes (e.g., [PtCl 4 ] 2− and [PtCl 6 ] 2− ) to become competitive with PtO generation. 38 Second, we found in our earlier work 17 that the electrogenerated [MIMAcO-T + − OH − ] adduct repels OH − , which may cause ΔpH local to deviate from the theoretically expected results. These two factors may contribute to the difference between the experimental and simulated results, which are reflected in the relatively large error bars in Figure 5f.…”
Section: Determination Of Ph Local Affected By Oxidation Of Mimaco-t ...mentioning
confidence: 79%
“…The molecular structures of 4-OH-T and MIMAcO-T are shown in Figure a. MIMAcO-T is a Bro̷nsted acid, which liberates protons upon hydrolysis to form [MIMAcO-T–OH – ] MIMAcO normalT + H 2 normalO false[ MIMAcO normalT OH false] + H + …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations